From protection to persecution: exploring the impact of anti-foreigner mobilisation on refugee rights in South Africa - Finger, Boitumelo (Department of Public Law, 2025)
This research explores how anti-foreigner mobilisation impedes the rights and lives of refugees in South Africa. This study does this by highlighting the anti-foreigner mobilisation movement, Operation Dudula. Grounded in a qualitative desk review, the study examines the systemic, social and economic impacts of xenophobia on the refugee communities. Many of the rights of refugees, who have legal rights to protection under international conventions, including the 1951 Refugee Convention and domestic laws such as the Refugees Act of 1998, are being violated. These violations take the form of violence, economic exclusion and social exclusion, usually enabled by scapegoating and misinformation. This research explores the need for multifaceted interventions to mitigate anti-foreigner mobilisation and its negative implications among refugee communities in South Africa. The South African administration must respond to the structural motivators of xenophobia and fortify the legal protections that come with the status of refugees through the implementation of constitutional ideals and international obligations. Addressing the root causes of forced displacement, such as conflict and poverty, requires a human rights-based approach that emphasises prevention, protection and empowerment. In conclusion, this study highlights the importance of collaboration between state and non-state actors, as well as local and international entities, to ensure a rights-based approach to refugee protection, in line with the highest international standards. Through decisive action, South Africa is able to reaffirm its position as a beacon of human rights and solidarity in the region.